Critical Synthesis Package: Four Habits Coding Scheme (4HCS) - Yoon Soo Park; Ara Tekian (Association of American Medical Colleges, 2013)
Abstract The Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Four Habits Coding Scheme (4HCS), and (2) a copy of the 4HCS instrument developed by Edward Krupat, PhD, Richard Frankel, and Terry Stein. The 4HCS measures communication skills based on the Four Habits Model. It contains 23 items, divided into four Habit subscales: (1) Invest in the Beginning (measure of ability to create rapport quickly and plan the visit), (2) Elicit the Patient's Perspective (measure of patient's understanding of the problem, goals for the visit, and ability to determine the impact of the problem on the patient's life), (3) Demonstrate Empathy (measure of encouragement, acceptance, and response to patient's expression of emotion), and (4) Invest in the End (measure of effective decision making and information sharing). Each item is scored on a 5-point behaviorally anchored rating scale, where the 4HCS provides definitions of the middle and end categories. Scores for each habit is determined by averaging or summing ratings across items in each subscale and higher scores indicate greater communication skill. Items are based on behaviors that require coders to process and judge several features on an ordinal scale, not a checklist based on frequencies. Validity evidence of the 4HCS has been presented in the original and subsequent studies. Users of this instrument should note that the high levels of inter-rater reliability (above 0.70) were obtained through rigorous rater training (18 hours). Additional validity evidence may be needed for 4HCS scores based on trainees at different stages of medical training and live observation.